New Uzbekistan: Issues of Social Services for The Elderly People - Yusupov Rakhimjon Karimovich; Kodirov Obid Safarovich (Zien Journals, 2021)
The article studies the problems of social gerontology of New Uzbekistan. Various social groups and communities of the elderly and old people are being investigated. It was found that on the basis of socio-demographic facts, it is necessary to develop issues of social protection of the elderly. In the conclusion, scientific recommendations for improving the work of the state form of management of social protection of the elderly and old people are presented
Keywords: New Uzbekistan; demographic truth; process; social gerontology